2019
DOI: 10.1080/24733938.2019.1612529
|View full text |Cite
|
Sign up to set email alerts
|

Pre-season training responses and their associations with training load in elite rugby league players

Abstract: Strength, power and endurance characteristics and their association with training load during a 7-week preseason training phase was assessed in elite rugby league players. Twenty-two players (age 23.3 ± 4.4 years) performed bench throw, one repetition maximum (1RM) bench press, squat jumps, three repetition maximum (3RM) squats, prone pull ups and prone Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) before and after the 7-week preseason period. Training was classified into Gym, Field and Wrestle, with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…Based on the collective findings following the preseason, a greater increase in lower body strength was observed when players lifted predominantly heavier loads ( 80% 1 RM) during resistance training sessions (Figure 2; A) over five -eight weeks, completing two -four sessions per week (Comfort et al, 2012;de Lacey et al, 2014a;Harris et al, 2008;O'Connor and Crowe, 2007;Rogerson et al, 2007). During the pre-season concurrent training load is at its peak and this along with the concomitant lighter lower body resistance training loads, appears to result in smaller improvements in lower body strength (Table 1) (Daniels et al, 2019;Harris et al, 2008). Moreover, superior increases in upper body pushing strength may be attributed to prescription of lower repetitions and higher loads (Table 1) (O'Connor and Crowe, 2007;Rogerson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the collective findings following the preseason, a greater increase in lower body strength was observed when players lifted predominantly heavier loads ( 80% 1 RM) during resistance training sessions (Figure 2; A) over five -eight weeks, completing two -four sessions per week (Comfort et al, 2012;de Lacey et al, 2014a;Harris et al, 2008;O'Connor and Crowe, 2007;Rogerson et al, 2007). During the pre-season concurrent training load is at its peak and this along with the concomitant lighter lower body resistance training loads, appears to result in smaller improvements in lower body strength (Table 1) (Daniels et al, 2019;Harris et al, 2008). Moreover, superior increases in upper body pushing strength may be attributed to prescription of lower repetitions and higher loads (Table 1) (O'Connor and Crowe, 2007;Rogerson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, two studies reported a large increase in relative peak power (de Lacey et al, 2014a;O'Connor and Crowe, 2007) (Table 1). One study reported small increases in bench throw peak power (Daniels et al, 2019). The meta-analysis of three lower body power studies (Figure 2; C) showed an overall moderate increase and low non-significant heterogeneity of studies (I 2 = 0%; p = 0.64).…”
Section: Pre-seasonmentioning
confidence: 92%
See 3 more Smart Citations